G5P4A0 HAMIL 28 MINGGU DENGAN PARTUS PREMATURUS IMMINENS (PPI) - Shariff, Fonda Octarianingsih; Irhamna, Teguh (CV. Jasa Sukses Abadi, 2024)
Prematurity Iminens is a threat to pregnancy where signs of labor appear at preterm gestational age (20 weeks – 37 weeks) and the baby's birth weight is less than 2500 grams. In a patient with G5P4A0 28 weeks pregnant with complaints of lower abdominal pain and cramps. Complaints accompanied by blood coming out of the birth canal at 14.00 WIB, BAK and defecation felt painful. Imminent premature parturition is a threat to pregnancy where signs of labor appear at preterm gestational age (20 weeks – 37 weeks) and the baby's birth weight is less than 2500 grams. Imminens premature labor is diagnosed with contractions that repeat at least once every 7-8 minutes, or 2-3 times within 10 minutes, pain in the lower back, spotting bleeding, feeling of pressure on the cervix. Pregnant women who are at risk of preterm labor and/or showing signs of preterm labor need intervention to improve neonatal outcomes. The conclusion has been established through a working diagnosis of G5P4A0 28 weeks pregnant with Partus Prematurus Imminens (PPI) based on clinical considerations, physical examination findings, and supporting examinations. Several types of drugs that can be given as tocolysis are calcium antagonists, for example Nifedipine 10 mg/oral repeated 2-3 times/hour, continued every 8 hours until contractions disappear and can be given again if contractions recur and the maintenance dose is 3 x 10 mg. Other alternative medications are other types of β-mimetics such as salbutamol, terbutaline, rithrodine and soxuprin or magnesic sulfate (MgSO4) and antiprostaglandins (indomethacin), but these are rarely used because of side effects on the mother or fetus. The aim of providing corticosteroid therapy is to mature fetal lung surfactant, reduce the incidence of RDS, prevent intraventricular bleeding, which ultimately can reduce the risk of neonatal death. Corticosteroids need to be given if the gestational age is <35 weeks. The drugs that can be given are dexamethasone (at a dose of 4 x 6 mg i.m with a 12 hour interval) or bexamethasone (at a dose of 2 x 12 mg i.m with a 24 hour administration interval).